Effects of Recombinant Human Erythropoietin (rHuEpo) on the Blood Cells and Hematopoiesis in Spleen of Rats (Journal of Sciences, Islamic Republic of Iran)
Recombinant human erythropoietin is a glycoprotein hormone that stimulates erythropoiesis. In clonogenic assays of hematopoietic progenitors, high concen-trations of erythropoietin (Epo) increase CFU-E and diminish the number of granulocytes formed per culture plate. Fetal progenitors are more sensitive to these effects of Epo than progenitors from adults. We administered doses 50, 100, 200 IU/kg of rHuEpo, subcutaneously, twice a week for six weeks. rHuEpo recipients had elevations in RBCs and reductions in WBCs, and platelet count, as well as in spleen (p